Direct visualization and 3D reconstruction of conductive filaments in aSiO2 material-based memristive device - Šlang, Stanislav; Gu, Bin; Zhang, Bo; Janíček, Petr; Rodriguez Pereira, Jhonatan; Wágner, Tomáš (Royal Society of Chemistry, 2024)
Observation of conductive filaments has greatly aided the development of theoretical models of memristive devices. In this work, we visualized and reconstructed the conductive filaments in a Cu/Cu-doped SiO2/W device employing a focused ion beam (FIB) as a milling technique. The SEM images taken from the device after 150 DC sweep cycles showed that Joule heat played a vital role in determining the morphology of a conductive filament, where the vaporization of the conductive filament resulted in the creation of defects, including particles, voids, and cavities. The competition between the formation and vaporization of conductive filaments generally induces a remarkable current fluctuation. Since Cu-doped SiO2 was utilized as the electrolyte, the vapors exfoliated adjacent single layers. FIB milling proceeded in top-down and front-back modes; thus, a 3D model of conductive filaments and defects was constructed according to a series of FIB-SEM images. This methodology is promising for a future failure analysis of memristive devices.
Přímá vizualizace a 3D rekonstrukce vodivých vláken v memristivním zařízení na bázi SiO2
Keywords: performance; výkonnost